IoT platform for personal data protection - Suciu, George (Array, 2020)
Since the establishment of IoT (Internet of Things), a variety of end devices become interconnected with one another, and thus, new types of security challenges appeared which have to be taken care of. Personal data, at the moment, have a higher risk of being hacked by various types of cyberattacks, as a result of the abundance of connectivity in the cloud realm. To face this type of challenges, the European Union decided to implement in 2018 the GDPR (General Data Protection Regulation) that implies that personal data of any kind can be shared with a third party only with their accord and can be, as well, deleted by them, whenever they desire. Henceforth, this paper introduces the PARFAIT project that will take into account this regulation and will integrate a platform with the purpose of protecting the personal data in IoT based applications, especially for smart home, smart office and smart hotel use cases.